Development of Communicative Behavior and Student Engagement of Students Using Integration of Transformative - Ugsornwong, Rosewalee (Ubon Ratchathani Journal of Research and Evaluation, 2020)
The purposes of this research were to study of effect of communicative behavior and student engagement of the experiment group before and after participation in integrated learning of transformative learning and experiential learning. The participants in this research consisted of 50 students of Faculty of Education, Ubon Ratchathani Rajabhat University using cluster random sampling. The research instruments were lesson plans with content validity ranging from 0.75-1.00; communicative behavior scale with content validity ranging from 0.67-1.00, discrimination powers ranging from 0.21 to 0.57 and the reliability of 0.75; and student engagement scale with content validity ranging from 0.67-1.00, discrimination powers ranging from 0.23. to 0.73 and the reliability of 0.87. The research design in this study was Quasi-experimental research, with Randomized Control-Group Pretest-Posttest Design. The data were analyzed using Multivariate Analysis of Covariance: One way MANCOVA) The research findings were as follows: There was significant difference of communicative behavior and student engagement between students in the experiment group and control group at the .05 level. (Wilks’ Lambda=0.257, F=7.782, p < .05) By using Univariate test, the students in the experiment group get more scores on communicative behavior than students in the control group at .05 significant level.